DEIKSIS PERSONA DALAM FILM DOKUMENTER DIRTY VOTE DAN IMPLEMENTASINYA PADA PEMBELAJARAN BAHASA INDONESIA DI SMA - Salsabil Najwa Azhari; Dase Erwin Juansah; Erwin Salpa Riansi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to describe the use of personal deixis in the documentary film Dirty Vote and its implementation in Indonesian language learning for Grade XI high school students through a teaching module on short story writing. This research employed a qualitative method. The data were collected using observation techniques, including tapping, non-participatory observation, and note-taking. The data were derived from the utterances of Bivitri Susanti, Zainal Arifin Mochtar, and Feri Amsari in the documentary Dirty Vote directed by Dandhy Dwi Laksono. A total of 134 instances of personal deixis were identified, consisting of: (1) 29 first-person singular; (2) 71 first-person plural; (3) 8 second-person singular; (4) 12 third-person singular; and (5) 14 third-person plural deixis. Among these, the first-person plural deixis we appeared most frequently. Its use indicates inclusivity, in which the speaker involves the second person (the audience) in the conversation. In this study, the use of we serves as a rhetorical strategy by Bivitri, Zainal, and Feri to make the audience feel involved and become part of the film.